PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUIZ TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII3 SMPN 2 KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Ningsih, Silvia - (STKIP PGRI Sumbar, 2014)
This research was motivate by comprehension of mathematical concepts students are still low and the responsibility of students in mathematics learning is still lacking. The aims of this study to determine the students understanding of mathematical concepts with apply the active learning strategies to influence the type of Quiz Team of grade VIII3 SMPN 2 Kecamatan Guguak Kabupaten Lima Puluh Kota after implemented active learning strategy of type Quiz Team. This type of research is the study of pre-experimental research design Pre-test and Post-test Group. The Subjects in the research is VIII3 SMPN 2 Kecamatan Guguak Kabupaten Lima Puluh Kota. From the research that has been done shows the average post-test score of students (71.72) is higher than the average pre-test score of students (29.97). It is proved that there was an effect of the use of active learning of strategies types Quiz Team of student understanding of mathematical concepts. In addition, hypothesis testing using t-test were put forward by Arikunto (2010 : 124) obtained t value of 13.22 > ttable is only 2.06, the hypothesis accepted. It can be conclude that were significant implementation of active learning strategies type Quiz team of students comprehension of mathematical concepts in class VIII3 SMPN 2 Kecamatan Guguak Kabupaten Lima Puluh Kota.